2022
DOI: 10.3389/fonc.2022.826778
|View full text |Cite
|
Sign up to set email alerts
|

Germline Mutations in Patients With Early-Onset Prostate Cancer

Abstract: ObjectiveTo investigate the inherited mutations and their association with clinical features and treatment response in young-onset prostate cancer patients.MethodTargeted gene sequencing on 139 tumor susceptibility genes was conducted with a total of 24 patients diagnosed with PCa under the age of 63 years old. Meanwhile, the related clinical information of those patients is collected and analyzed.ResultsSixty-two germline mutations in 45 genes were verified in 22 patients. BRCA2 (20.8%) and GJB2 (20.8%) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Similarly, we showed that patients with bilateral or multifocal nccRCC are more likely to have pathogenic/likely pathogenic germline mutations. Early-onset cancer is a hallmark of an inherited cancer predisposition (35,36), and studies have shown that patients with mutations in RCC-associated genes, such as VHL, FH, FLCN, and SDHB, are at risk for the development of early-onset RCC (37)(38)(39). Loss of function of MUTYH accounts for 3% of early-onset CRC (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we showed that patients with bilateral or multifocal nccRCC are more likely to have pathogenic/likely pathogenic germline mutations. Early-onset cancer is a hallmark of an inherited cancer predisposition (35,36), and studies have shown that patients with mutations in RCC-associated genes, such as VHL, FH, FLCN, and SDHB, are at risk for the development of early-onset RCC (37)(38)(39). Loss of function of MUTYH accounts for 3% of early-onset CRC (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Targeted sequencing of 139 cancer-related genes in 24 patients under the age of 63 years with PC revealed a total of 62 germline mutations in 45 genes; 22/24 patients harbored germline mutations, and nearly 60% of patients had mutations in DDR genes. BRCA2 (20.8%) and gap junction beta-2 ( GJB2 ) (20.8%) were the most frequently mutated genes [ 44 ]. Mutations in CHEK2 , BRCA1 , PALB2 , cyclin-dependent kinase inhibitor 2A ( CDKN2A ), homeobox protein B13 ( HOXB13 ), protein phosphatase 1D ( PPM1D ), and ATP-dependent DNA helicase Q1 ( RECQL ) were also common (8.3% each) [ 44 ].…”
Section: Role Of the Hrr Pathway In Pcmentioning
confidence: 99%
“…BRCA2 (20.8%) and gap junction beta-2 ( GJB2 ) (20.8%) were the most frequently mutated genes [ 44 ]. Mutations in CHEK2 , BRCA1 , PALB2 , cyclin-dependent kinase inhibitor 2A ( CDKN2A ), homeobox protein B13 ( HOXB13 ), protein phosphatase 1D ( PPM1D ), and ATP-dependent DNA helicase Q1 ( RECQL ) were also common (8.3% each) [ 44 ]. Another targeted sequencing study of 18 DDR genes in 316 patients with PC showed that 9.8% of patients had pathogenic germline mutations in 18 DDR genes [ 45 ].…”
Section: Role Of the Hrr Pathway In Pcmentioning
confidence: 99%
“…Recent studies indicate that RECQs may serve as potential genes responsible for breast cancer susceptibility, with missense mutations in these genes playing a role in the development of familial breast cancer [ 15 , 16 , 17 ]. In addition, RECQs are linked to thyroid carcinoma, prostate cancer, and ovarian cancer [ 18 , 19 ]. RECQs play a wide-ranging and varied role in the regulation of cancer and are closely associated with renowned molecules or pathways that control cancer, thereby having significant implications for cancer treatment [ 20 ].…”
Section: Introductionmentioning
confidence: 99%